Manipulation Analysis Sport Massage On Decreased Heart Rate After Swimming 100-Meter Freestyle - Roepajadi, Joesoef; Nurmaya, Ika; Purbodjati; Wahyudi, Heri; Januardi Irawan, Roy (PT. Hafasy Dwi Nawasena, 2024)
Swimming 100 meters freestyle could increase heart rate and blood pressure because the body needs to meet oxygen intake. Excessive increase in pulse rate could be harmful to health. This study aims to determine the difference in heart rate after swimming 100 meters freestyle, without manipulation, and after sports massage. This research was conducted using quantitative research methods in the form of comparative methods. Research data was collected through interviews and observations. The population in this study were students of the class of 2023 swimming course at the State University of Surabaya. Sampling was carried out using purposive sampling with inclusion criteria, namely 1) Male; 2) Age between 19-24 years; 3) 3 days before did not act eccentric exercise; 4) Carrying out a 100-meter freestyle swim at the research location to obtain 30 respondents. Data collection was carried out using a questionnaire and recording the results of pulse measurements using a pulse meter. The results show that there is a difference in the decrease in heart rate between the first measurement without manipulation and the second measurement with sports massage manipulation. The test results state that there is a significant effect between exercise massage and a decrease in the pulse rate of athletes swimming in the 100-meter freestyle with a P-value of 0.001.